Pendidikan dan Stratifikasi Sosial Di TK Darun Najah Sangatta Selatan: Analisis Peran Lembaga Paud Dalam Membangun Kesetaraan Sosial - Nurainiya Maghfiroh; Muhammad Yasin (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2026)
Education and social stratification are two interrelated concepts in research on society and education. Education does not merely serve as a tool for transferring knowledge and skills, but also plays an important role in shaping the social structure within a community. The focus of this study is: What is the form of social stratification at Darun Najah Kindergarten in South Sangatta, what is the role of social stratification at Darun Najah Kindergarten in South Sangatta, and what factors support and hinder social stratification at Darun Najah Kindergarten in South Sangatta. The methodology used in this research is a qualitative approach, which includes a literature review and analysis of secondary data from various relevant empirical sources and interviews. The findings from the analysis show that social stratification at Darun Najah Sangatta Selatan Kindergarten is formed through several layers or categories that arise from differences in roles, status, and responsibilities within the school environment. Social stratification in the Darun Najah Sangatta Selatan Kindergarten environment has several important roles, such as helping to divide tasks and responsibilities, creating effective coordination, and increasing the professionalism of teachers and staff. The main factors causing social inequality include suboptimal budget allocation, unequal access to educational facilities, and economic inequality among families, which limits their ability to pay for their children's education. This is because Darun Najah Kindergarten still lacks the infrastructure and resources to support learning activities to ensure that children receive a better and fairer education